Method for extracting dissolved polar substances from transformer oil using a functionalized solid adsorbent

CN123028863APending Publication Date: 2026-11-03JILIN ELECTRIC POWER RES INST LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611352219.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing technologies are difficult to effectively enrich dissolved polar substances in transformer oil, and suffer from problems such as poor selectivity, strong oil phase residue, low enrichment efficiency, and insufficient repeatability.

Method used

By employing functionalized solid-phase adsorbents combined with low-polarity dilution, selective adsorption, oil removal pre-washing, and gentle elution processes, the functionalized solid-phase adsorbents selectively act on target polar substances. Combined with the use of low-polarity diluents, pre-washing agents, and eluents, the efficient enrichment of dissolved polar substances is achieved.

Benefits of technology

It significantly improves the single-pass processing efficiency of dissolved polar substances, reduces oil phase background interference, has strong adaptability, can perform targeted enrichment of different types of polar substances, and provides stable sample pretreatment technology support.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123028863A_ABST
    Figure CN123028863A_ABST
Patent Text Reader

Abstract

The present application relates to transformer oil detection, oil-paper insulation state evaluation and sample pretreatment technical field, especially to a kind of functional solid phase adsorbent extraction method of dissolved polar substance in transformer oil.Polar substance dissolved in the content of running transformer oil is low, and oil matrix composition is complex, existing pretreatment method has the problems of poor selectivity, strong oil phase residue, low enrichment efficiency and insufficient repeatability, the present application is sequentially treated by oil sample constant temperature homogenization, low polarity dilution, functional solid phase adsorbent adsorption, solid-liquid separation, low polarity prewash oil, polar elution and concentration constant volume, to realize the selective enrichment of dissolved polar substance in oil.The present application can effectively reduce the background interference of non-polar oil phase, improve the enrichment efficiency and method stability, and provide reliable pretreatment technology support for oil-paper insulation deterioration state evaluation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of transformer oil testing, oil-paper insulation condition assessment, and sample pretreatment technology, and particularly to a method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent. Background Technology

[0002] During long-term operation, oil-immersed power transformers are subjected to the combined effects of heat, electricity, oxygen, moisture, metallic materials, corrosive sulfur, microorganisms, and aging products, gradually generating various polar contaminants. In addition to particulate and colloidal contaminants, operating transformer oil also contains polar substances dispersed in the oil phase in dissolved form. These substances typically include acidic oxidation products, oxygen-containing small-molecule aging products, sulfur-containing polar compounds, nitrogen-containing polar compounds, plasticizers, insulating material leachates, polar components related to microbial metabolism, and soluble organometallic complexes. Although dissolved polar substances may not necessarily appear as visible particles, their impact on the oil-paper insulation system is quite significant. Acidic oxidation products and oxygen-containing polar small molecules can increase the dielectric loss factor and conductivity in oil, promoting the hydrolysis of insulating paper and the breakage of cellulose chains. Plasticizers and solvents from insulating materials may alter the interfacial properties of oil-paper. Sulfur-containing polar compounds and soluble organometallic complexes can interact with metal components, insulating paper fibers, and aging products in oil, further inducing the accumulation of polar contaminants. Under varying temperature, electric field, and moisture conditions, some dissolved polar substances may also transform into colloidal or particulate contaminants, becoming important precursors to the deterioration of oil-paper insulation.

[0003] Currently, transformer oil condition assessment relies heavily on indicators such as acid value, trace water content, breakdown voltage, dielectric loss factor, dissolved gases, furfural, and metal content. While these indicators reflect the overall deterioration trend of the oil, they are insufficient to directly obtain the enrichment characteristics of dissolved polar substances. For low-content dissolved polar substances in complex non-polar oil matrices, direct solvent dilution, rotary evaporation concentration, or liquid-liquid extraction can easily lead to problems such as simultaneous enrichment of the oil phase background, insufficient extraction selectivity, high solvent consumption, and poor repeatability. Especially in operating transformer oils, the sources of dissolved polar substances are complex and their content is low, making stable enrichment difficult to achieve with conventional pretreatment methods. Summary of the Invention

[0004] The purpose of this invention is to provide a method for enriching and extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent, thereby solving the problems of poor selectivity, strong oil phase residue, low enrichment efficiency, and insufficient repeatability of existing liquid-liquid extraction, direct concentration, or ordinary adsorption methods for dissolved polar substances. The specific technical solution is as follows:

[0005] A method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent includes the following steps:

[0006] S1. Constant temperature homogenization treatment of oil sample: Take 5-100mL of operating transformer oil sample, place it in a container, and treat it at a constant temperature of 25-55℃ for 5-30min to make the oil sample homogenized.

[0007] S2. Low polarity dilution: Add a low polarity diluent to the oil sample to obtain a diluted oil sample; the volume ratio of the low polarity diluent to the operating transformer oil sample is 1:1 to 3:1.

[0008] S3. Solid-phase adsorption: Add functionalized solid-phase adsorbent to the diluted oil sample, and control the adsorption temperature at 25-50℃ and the adsorption time at 10-90min; the mass-to-volume ratio of the functionalized solid-phase adsorbent to the operating transformer oil sample taken in step S1 is 5-50mg / mL.

[0009] S4. Adsorbent separation: Through solid-liquid separation, the functionalized solid-phase adsorbent loaded with dissolved polar substances is separated from the diluted oil after adsorption to obtain the loaded adsorbent.

[0010] S5. Degreasing and pre-washing: The loaded adsorbent is washed 1 to 2 times with a low polarity pre-washing agent, with each washing time being 10 to 20 minutes, to remove the transformer oil and non-polar components remaining on the surface of the adsorbent, and to obtain the pre-washed adsorbent.

[0011] S6. Polar elution: The pre-washed adsorbent is eluted with an eluent to obtain a solution of dissolved polar substances.

[0012] S7. Enrichment solution treatment: The enrichment solution is concentrated and brought to a constant volume to obtain a solution of dissolved polar substances for subsequent detection. The concentration temperature is 25-45℃.

[0013] Furthermore, the low-polarity diluent is one or more of n-hexane, n-heptane, isooctane, petroleum ether, or cyclohexane.

[0014] Furthermore, the functionalized solid-phase adsorbent is selected from one or more of amino-containing adsorbents, aromatic porous polymer adsorbents, and chelating adsorbents containing thiol or pyridyl groups.

[0015] Furthermore, the amino-containing adsorbent is aminated silica or polyethyleneimine-modified silica gel;

[0016] The aromatic porous polymer adsorbent is a styrene-divinylbenzene copolymer;

[0017] The thiol- or pyridyl-containing chelating adsorbent is a thiol-based silica gel, a pyridyl resin, or a polydopamine-modified adsorbent.

[0018] Furthermore, the functionalized solid-phase adsorbent is a composite functionalized solid-phase adsorbent, which is obtained by mixing aminated silica, styrene-divinylbenzene copolymer and mercaptosilicone in a mass ratio of 1:(0.5-2):(0.2-1).

[0019] Furthermore, the low-polarity pre-washing agent is one or more of hexane, heptane, isooctane, or petroleum ether; the amount of low-polarity pre-washing agent used is 0.5 to 2.0 mL per 100 mg adsorbent.

[0020] Furthermore, the eluent is one or more of methanol, ethanol, isopropanol, ethyl acetate, ethanol-water mixture, methanol-water mixture, alcohol solution containing 0.1-1.0 vol.% formic acid, and alcohol solution containing 0.1-1.0 vol.% ammonia.

[0021] Furthermore, the volume fraction of water in the ethanol-water mixture or methanol-water mixture is 5-30 vol.%; the amount of eluent used is 0.3-2.0 mL per 100 mg adsorbent, eluting 1-2 times, with each elution time being 5-30 min.

[0022] Furthermore, the concentration and volume adjustment process is carried out by nitrogen purging or low-temperature rotary evaporation.

[0023] Furthermore, the extract is used for the detection of polar contaminants, and the detection methods include Fourier transform infrared spectroscopy, gas chromatography-mass spectrometry, liquid chromatography, liquid chromatography-mass spectrometry, ultraviolet spectroscopy, and total acid value detection.

[0024] The beneficial effects of this invention are as follows:

[0025] 1. This invention uses functionalized solid-phase adsorbents as the core, combined with low polarity dilution, selective adsorption, oil removal pre-washing and gentle elution processes. Compared with ordinary liquid-liquid extraction, it does not rely on a large amount of polar solvent. It can selectively act on target polar substances through functional sites on the surface of the adsorbent, effectively reduce oil phase background interference, and significantly improve the apparent enrichment efficiency of a single treatment.

[0026] 2. The present invention can flexibly adjust the composition of the adsorbent according to the type of the target dissolved polar substance. For different objects such as acidic oxidation products, plasticizers, sulfur-containing polar substances, and soluble metal complexes, a single functional adsorbent can be selected to complete the directional enrichment, or multiple adsorbents can be combined to extract multiple types of dissolved polar substances simultaneously, which has strong adaptability.

[0027] 3. The enriched solution obtained by this invention can be adapted to a variety of subsequent detection and analysis methods, and can provide stable and reliable sample pretreatment technology support for the study of the degradation mechanism of transformer oil-paper insulation, the identification of the source of polar contaminants in oil, and the fault diagnosis of reduced insulation resistance. Attached Figure Description

[0028] Figure 1 This is a schematic diagram illustrating the steps of a method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent according to the present invention. Detailed Implementation

[0029] A method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent includes the following steps:

[0030] S1. Constant temperature homogenization treatment of oil sample: Take 5-100mL of the oil sample from the operating transformer, place it in a container, and treat it at a constant temperature of 25-55℃ for 5-30min to make the oil sample homogenized.

[0031] S2. Low polarity dilution: Add a low polarity diluent to the oil sample to obtain a diluted oil sample; the volume ratio of the low polarity diluent to the operating transformer oil sample is 1:1 to 3:1.

[0032] S3. Solid-phase adsorption: Add functionalized solid-phase adsorbent to the diluted oil sample, and control the adsorption temperature at 25-50℃ and the adsorption time at 10-90min; the mass-to-volume ratio of the functionalized solid-phase adsorbent to the operating transformer oil sample taken in step S1 is 5-50mg / mL.

[0033] S4. Adsorbent separation: Through solid-liquid separation, the functionalized solid-phase adsorbent loaded with dissolved polar substances is separated from the diluted oil after adsorption to obtain the loaded adsorbent.

[0034] S5. Degreasing and pre-washing: The adsorbent after loading is washed 1 to 2 times with a low polarity pre-washing agent, with each washing time being 10 to 20 minutes, to remove the transformer oil and non-polar components remaining on the surface of the adsorbent, and to obtain the pre-washed adsorbent.

[0035] S6. Polar elution: The pre-washed adsorbent is eluted with an eluent to obtain a solution of dissolved polar substances.

[0036] S7. Enrichment solution treatment: The enrichment solution is concentrated and brought to a constant volume to obtain a solution of dissolved polar substances for subsequent detection. The concentration temperature is 25-45℃.

[0037] The low-polarity diluent is one or more of n-hexane, n-heptane, isooctane, petroleum ether, or cyclohexane.

[0038] The functionalized solid-phase adsorbent is selected from one or more of the following: amino-containing adsorbents, aromatic porous polymer adsorbents, thiol- or pyridyl-containing chelating adsorbents, and cyclodextrin-modified adsorbents.

[0039] Amino-containing adsorbents include aminated silica, polyethyleneimine-modified silica gel, weak anion exchange resin, or aminated alumina.

[0040] Aromatic porous polymer adsorbents are styrene-divinylbenzene copolymers, porous polymer resins, or phenyl-bonded silica gel;

[0041] The chelating adsorbents containing thiol or pyridyl groups are thiol silica gel, pyridyl resin, iminodiacetic acid resin, or polydopamine-modified adsorbents;

[0042] The cyclodextrin-modified adsorbent is β-cyclodextrin-modified silica gel or β-cyclodextrin-modified polymer microspheres.

[0043] Functionalized solid-phase adsorbents can also be composite functionalized solid-phase adsorbents, which are obtained by mixing aminated silica, styrene-divinylbenzene copolymer and mercaptosilicone in a mass ratio of 1:(0.5~2):(0.2~1).

[0044] The low-polarity pre-washing agent is one or a mixture of n-hexane, n-heptane, isooctane or petroleum ether; the amount of low-polarity pre-washing agent used is 0.5 to 2.0 mL per 100 mg adsorbent.

[0045] The eluent is one or more of the following: methanol, ethanol, isopropanol, ethyl acetate, ethanol-water mixture, methanol-water mixture, alcohol solution containing 0.1 to 1.0 vol.% formic acid, and alcohol solution containing 0.1 to 1.0 vol.% ammonia.

[0046] The volume fraction of water in the ethanol-water mixture or methanol-water mixture is 5-30 vol.%; the amount of eluent used is 0.3-2.0 mL per 100 mg adsorbent, and elution is performed 1-2 times, with each elution time being 5-30 min.

[0047] The concentration and volume adjustment process is carried out by nitrogen purging or low-temperature rotary evaporation.

[0048] The extract is used for the detection of polar contaminants, and the detection methods include Fourier transform infrared spectroscopy, gas chromatography-mass spectrometry, liquid chromatography, liquid chromatography-mass spectrometry, ultraviolet spectroscopy, and total acid value detection.

[0049] like Figure 1 As shown, this invention proposes an embodiment of a method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent, comprising the following steps:

[0050] S1. Oil sample isothermal homogenization treatment

[0051] Take 5–100 mL of operating transformer oil sample and place it in a clean glass or PTFE container. Incubate at 25–55°C for 5–30 minutes to ensure homogenization. The preferred sample volume is 10–30 mL; for rapid on-site screening, 5–10 mL is acceptable; for samples with low dissolved polar substance content, 50 mL is recommended to ensure enrichment. The preferred incubation temperature is 35–45°C, and the preferred incubation time is 10–20 minutes. Too low a temperature results in high oil viscosity, hindering adsorbent dispersion; too high a temperature may cause some low-molecular-weight polar components to volatilize, or weakly bound complexes to dissociate, affecting enrichment accuracy.

[0052] S2, Low polarity dilution

[0053] Add a low-polarity diluent to the oil sample obtained in step S1 to obtain a diluted oil sample; the volume ratio of the low-polarity diluent to the operating transformer oil sample is 1:1 to 3:1; the low-polarity diluent is one or more of n-hexane, n-heptane, isooctane, petroleum ether, or cyclohexane. Preferably, the low-polarity diluent is n-heptane or isooctane, and the volume ratio of the low-polarity diluent to the oil sample is preferably 2:1. If the dilution ratio is too low, the viscosity of the oil sample will not decrease sufficiently, which will affect the contact efficiency between the adsorbent and the oil sample; if the dilution ratio is too high, the total sample volume will be too large, and the dissolved polar substances will be over-diluted, leading to an increase in the amount of adsorbent used and the treatment time.

[0054] S3, solid-phase adsorption

[0055] Add functionalized solid-phase adsorbent to the diluted oil sample obtained in step S2, and control the adsorption temperature at 25-50℃ and the adsorption time at 10-90 min; the mass-to-volume ratio of functionalized solid-phase adsorbent to the operating transformer oil sample taken in step S1 is 5-50 mg / mL; during the adsorption process, oscillation or stirring is used to enhance the adsorption operation; when oscillation is used, the oscillation frequency is 100-300 rpm; when stirring is used, the stirring speed is 300-800 rpm.

[0056] Functionalized solid-phase adsorbents include one or more of the following: amino-containing adsorbents, aromatic porous polymer adsorbents, thiol- or pyridyl-containing chelating adsorbents, and cyclodextrin-modified adsorbents. Specifically, amino-containing adsorbents are aminated silica, polyethyleneimine-modified silica gel, weak anion exchange resins, or aminated alumina; aromatic porous polymer adsorbents are styrene-divinylbenzene copolymers, porous polymer resins, or phenyl-bonded silica gel; thiol- or pyridyl-containing chelating adsorbents are thiol-modified silica gel, pyridyl resins, iminodiacetic acid resins, or polydopamine-modified adsorbents; and cyclodextrin-modified adsorbents are β-cyclodextrin-modified silica gel or β-cyclodextrin-modified polymer microspheres.

[0057] The functionalized solid-phase adsorbent is preferably a composite functionalized solid-phase adsorbent, which is obtained by mixing aminated silica, styrene-divinylbenzene copolymer and mercaptosilicone in a mass ratio of 1:(0.5~2):(0.2~1). Among them, aminated silica is mainly used to adsorb acidic oxidation products and oxygen-containing polar small molecules, styrene-divinylbenzene copolymer is mainly used to adsorb plasticizers and aromatic polar components, and mercaptosilicone is mainly used to adsorb soluble copper-containing, iron-containing metal complexes or sulfur-containing polar components.

[0058] Regarding process parameters, the optimal mass-to-volume ratio of functionalized solid-phase adsorbent to the operating transformer oil sample is 10–30 mg / mL. If the adsorbent dosage is too low, there will be insufficient adsorption sites, leading to inadequate enrichment of dissolved polar substances. If the adsorbent dosage is too high, non-specific adsorption of low-polarity oil phases and non-target substances will increase, and the amount of eluent required for subsequent removal will also increase. The optimal adsorption temperature is 35–45℃, the optimal adsorption time is 30–60 min, the optimal oscillation frequency is 150–250 rpm, and the optimal stirring speed is 500–700 rpm.

[0059] S4, Adsorbent Separation

[0060] The functionalized solid-phase adsorbent loaded with dissolved polar substances is separated from the diluted oil after adsorption through solid-liquid separation to obtain the loaded adsorbent. The solid-liquid separation method adopts centrifugation, filtration, and magnetic separation. When centrifugation is used, the centrifugation speed is 3000-8000 rpm and the centrifugation time is 5-20 min, wherein the centrifugation speed is preferably 4000-6000 rpm and the centrifugation time is preferably 8-15 min. When filtration is used, the pore size of the filter membrane is 0.22-5.0 μm.

[0061] S5, Degreasing Pre-wash

[0062] The pre-loaded adsorbent obtained in step S4 is washed 1-2 times with a low-polarity pre-washing agent to remove residual transformer oil and non-polar components from the adsorbent surface, resulting in a pre-washed adsorbent. The low-polarity pre-washing agent is one or a mixture of n-hexane, n-heptane, isooctane, or petroleum ether, and the amount of pre-washing agent used is 0.5-2.0 mL per 100 mg of adsorbent. Preferably, the low-polarity pre-washing agent is n-heptane or isooctane, and the preferred amount is 0.8-1.5 mL per 100 mg of adsorbent, with 1-2 washes. The purpose of the low-polarity pre-wash is to remove residual oil phase from the adsorbent surface, not to elute the target dissolved polar substances; if the amount of pre-washing agent is too large or the number of washes is too many, some weakly adsorbed polar components may be lost.

[0063] S6, Polar Elution

[0064] The pre-washed adsorbent obtained in step S5 is eluted with an eluent to obtain a concentrated solution of dissolved polar substances. The eluent is one or more of methanol, ethanol, isopropanol, ethyl acetate, ethanol-water mixture, methanol-water mixture, alcohol solution containing 0.1-1.0 vol.% formic acid, and alcohol solution containing 0.1-1.0 vol.% ammonia. The volume fraction of water in the ethanol-water mixture or methanol-water mixture is 5-30 vol.%. The amount of eluent used is 0.3-2.0 mL per 100 mg adsorbent, and elution is performed 1-2 times, with each elution time being 5-30 min.

[0065] The eluent should be selected specifically according to the type of target analyte: methanol, ethanol, or methanol containing 0.1–0.5 vol.% formic acid is preferred for acidic oxidation products and oxygen-containing polar molecules; ethyl acetate, methanol, or ethanol is preferred for plasticizers and aromatic polar components; ethanol or methanol containing 0.1–0.5 vol.% ammonia is preferred for soluble organometallic complexes and sulfur-containing polar components. The volume fraction of water in the alcohol-water mixture is preferably 5–15 vol.%. Strong acids or bases should not be used during the elution process to avoid damaging the target analyte structure or introducing interference into subsequent detection.

[0066] The preferred eluent dosage is 0.5–1.0 mL per 100 mg adsorbent, eluting 1–2 times, with each elution time preferably 10–20 min. Insufficient eluent will result in incomplete elution of the target polar component; excessive eluent will increase the volume of the enrichment solution, prolonging subsequent concentration time and potentially increasing the blank background.

[0067] S7, enrichment solution treatment

[0068] The enriched solution obtained in step S6 is concentrated and brought to a constant volume to obtain an extract of dissolved polar substances for subsequent detection. The concentration temperature is 25–45°C; the concentration method is nitrogen purging or low-temperature rotary evaporation. The obtained extract can be used for Fourier transform infrared spectroscopy, gas chromatography-mass spectrometry, liquid chromatography, liquid chromatography-mass spectrometry, ultraviolet spectroscopy, total acid value analysis, or detection of other polar contaminants. The enriched solution treatment temperature is preferably not to exceed 40°C. For enriched solutions that may contain low-molecular-weight aldehydes, ketones, alcohols, or low-molecular-weight acids, slow nitrogen purging or direct volume adjustment is preferred to avoid component loss due to high-temperature rotary evaporation.

[0069] Furthermore, in another embodiment of the present invention, the functionalized solid-phase adsorbent dispersed in steps S3 to S6 can be replaced with a packed solid-phase extraction column. The adsorbent loading in the solid-phase extraction column is 100–1000 mg, preferably 200–500 mg; the diluted oil sample obtained in step S2 is passed through the solid-phase extraction column at a flow rate of 0.2–3.0 mL / min to complete adsorption, preferably 0.5–1.5 mL / min. Oil pre-washing and polar elution operations are performed directly on the solid-phase extraction column sequentially, without the need for additional solid-liquid separation steps; the type, amount, and washing requirements of the low-polarity pre-washing agent are the same as in step S5, and the type, amount, and elution requirements of the polar eluent are the same as in step S6. The collected eluent is then concentrated and diluted to a fixed volume in step S7.

[0070] Furthermore, to verify the practical application effect and operational performance of the above-mentioned method for enriching and extracting dissolved polar substances from transformer oil using functionalized solid-phase adsorbents, several application examples and comparative examples are used for comparative verification. All application examples and comparative examples adopt a unified evaluation system, using the apparent primary enrichment rate of dissolved polar substances and the unit oil sample processing time as the core evaluation indicators. The evaluation process strictly follows the aforementioned operating procedures S1 to S7 to ensure the comparability of the results.

[0071] The apparent primary enrichment rate of dissolved polar substances is used to characterize the degree of enrichment of dissolved polar components in oil by the method during a single treatment process. Since the true total amount of dissolved polar substances in operating transformer oil is difficult to determine directly, and the elution residue may contain small amounts of non-target components, a continuous enrichment method is used for apparent evaluation. Specifically: Take the same operating transformer oil sample, complete the first adsorption, pre-washing, and elution according to steps S3 to S6, collect the first eluent, remove the solvent under the drying conditions in S7, and weigh it; then, the remaining oil phase after the first adsorption is subjected to the same method for the second and third enrichment processes, and the dried residual mass of the eluent is measured for each process. The apparent primary enrichment rate of dissolved polar substances is calculated using the following formula:

[0072] Apparent primary enrichment rate of dissolved polar substances = M1 / (M1+M2+M3)×100%;

[0073] In the formula, M1 is the mass increment of the eluent obtained from the first enrichment after solvent removal, and M2 and M3 are the mass increments of the corresponding eluents from the second and third enrichments after solvent removal, respectively; all mass increments have been reduced by the blank mass increment of the blank transformer oil after the same dilution, adsorption, pre-washing, elution and drying treatment to eliminate systematic errors.

[0074] To ensure the comparability of weighing results, all eluents were subjected to solvent removal and drying under uniform conditions: after the solvent was removed by nitrogen purging or low-temperature evaporation at 35–40°C, the eluents were vacuum dried at 40°C to constant weight; when the difference between two consecutive weighings did not exceed 0.2 mg, it was considered to have reached a constant weight state.

[0075] The unit oil sample processing time is used to characterize the operational efficiency of the enrichment process and is calculated using the following formula:

[0076] Unit oil sample processing time = Total time to complete a single adsorption, separation, pre-washing and elution process / Original transformer oil sample volume;

[0077] When processing operating transformer oil samples using the aforementioned method of this invention, the apparent primary enrichment rate of dissolved polar substances is not less than 70%, and under preferred conditions, not less than 80%. When processing 10–50 mL of operating transformer oil samples, the processing time per unit sample is not more than 3.0 min / mL, and under preferred conditions, not more than 2.0 min / mL. The following application examples cover various application scenarios, including different sample volumes, different types of functionalized adsorbents, composite adsorbent ratios, solid-phase extraction column modes, and magnetic adsorbents. The comparative examples, by adjusting the core process conditions and adsorbent materials, verify the necessity and technical superiority of each process step and the functionalized solid-phase adsorbent of this invention.

[0078] Application Example 1

[0079] This application example illustrates a conventional adsorption and enrichment method for dissolved polar substances in actual operating transformer oil.

[0080] Take 20 mL of actual operating transformer oil sample and keep it at 40℃ for 15 min. Add 40 mL of n-heptane to the oil sample to make the volume ratio of n-heptane to oil sample 2:1, and mix thoroughly to obtain a diluted oil sample.

[0081] Add 500 mg of a composite functionalized solid-phase adsorbent to the diluted oil sample. The composite functionalized solid-phase adsorbent is composed of aminated silica, styrene-divinylbenzene copolymer, and mercaptosilicone in a mass ratio of 1:1:0.5. Incubate the mixture at 40°C with shaking for 40 min at a shaking frequency of 200 rpm.

[0082] The solid-phase adsorbent was collected by centrifugation at 5000 rpm for 10 min. The adsorbent was pre-washed twice with 5 mL of n-heptane each time to remove residual oil phase. Subsequently, it was eluted twice with a 1:1 (v / v) methanol-ethyl acetate mixture, 2.5 mL each time, for 10 min each time. The eluents were combined, purged with nitrogen at 40 °C, and vacuum dried to constant weight to obtain a concentrate of dissolved polar substances.

[0083] According to the three-stage enrichment method, the apparent single enrichment rate of dissolved polar substances in this application example is 82.6%, and the unit oil sample treatment time is 1.8 min / mL.

[0084] Application Example 2

[0085] This application example illustrates an enrichment method under conditions of low oil sample volume and low adsorbent dosage.

[0086] Take 5 mL of actual operating transformer oil sample and let it stand at 25℃ for 10 min to ensure homogenization. Add 5 mL of isooctane to make the volume ratio of isooctane to oil sample 1:1. Add 50 mg of aminated silica to the diluted oil sample to make the mass-volume ratio of adsorbent to oil sample 10 mg / mL.

[0087] The adsorption temperature was 25℃, the adsorption time was 15 min, and the oscillation frequency was 100 rpm. After adsorption, the adsorbent was separated using a 0.22 μm filter membrane and pre-washed once with 0.5 mL of isooctane. Subsequently, it was eluted with 0.5 mL of methanol for 5 min, and the eluent was collected and dried under vacuum at 40℃ to constant weight to obtain a concentrate of dissolved polar substances.

[0088] According to the three-stage enrichment method, the apparent single enrichment rate of dissolved polar substances in this application example is 76.4%, and the unit oil sample treatment time is 2.8 min / mL.

[0089] Application Example 3

[0090] This application example illustrates a method for enriching faulty transformer oil samples with low levels of dissolved polar substances.

[0091] Take 50 mL of oil sample from the faulty transformer and keep it at 45℃ for 20 min. Add 150 mL of n-heptane to make the volume ratio of n-heptane to oil sample 3:1. Add 1.5 g of composite functionalized solid-phase adsorbent to the diluted oil sample to make the mass-volume ratio of adsorbent to oil sample 30 mg / mL.

[0092] The composite functionalized solid-phase adsorbent is composed of aminated silica, styrene-divinylbenzene copolymer, and mercaptosilicone in a mass ratio of 1:2:1. The adsorption temperature is 45℃, the adsorption time is 60 min, and the stirring speed is 700 rpm. The adsorbent is collected after centrifugation at 6000 rpm for 15 min.

[0093] The sample was prewashed twice with 15 mL of n-heptane each time. It was then eluted twice with 7.5 mL of methanol containing 0.5 vol.% formic acid each time, for 10 min each time. The eluates were combined, the solvent was removed at 40 °C, and the sample was vacuum dried to constant weight to obtain a concentrate of dissolved polar substances.

[0094] According to the three-stage enrichment method, the apparent single enrichment rate of dissolved polar substances in this application example is 81.2%, and the unit oil sample treatment time is 2.1 min / mL.

[0095] Application Example 4

[0096] This application example illustrates a method for the targeted enrichment of acidic oxidation products and oxygen-containing polar small molecules.

[0097] Take 20 mL of thermally aged transformer oil sample and keep it at 40℃ for 15 min. Add 40 mL of isooctane to make the volume ratio of isooctane to oil sample 2:1. Add 500 mg of polyethyleneimine modified silica gel and shake at 40℃ for 50 min at a shaking frequency of 200 rpm.

[0098] After adsorption, the adsorbent was separated by centrifugation and pre-washed twice with isooctane (5 mL each time). Then, it was eluted twice with methanol containing 0.5 vol.% formic acid (2.5 mL each time). The resulting eluent was dried under vacuum at 40 °C to constant weight to obtain a concentrate of dissolved polar substances.

[0099] According to the three-stage enrichment method, the apparent single enrichment rate of dissolved polar substances in this application example is 83.4%, and the unit oil sample treatment time is 2.0 min / mL.

[0100] Application Example 5

[0101] This application example illustrates a method for enriching plasticizers and aromatic polar components.

[0102] Take 30 mL of transformer oil sample containing plasticizer contamination risk and incubate at 35℃ for 10 min. Add 60 mL of n-heptane to make the volume ratio of n-heptane to oil sample 2:1. Add 900 mg of styrene-divinylbenzene porous polymer resin to the diluted oil sample and shake at 35℃ for 45 min at a shaking frequency of 250 rpm for adsorption.

[0103] After adsorption, the resin was collected by filtration using a 5.0 μm pore size filter membrane. It was pre-washed twice with 9 mL of n-heptane each time. Subsequently, it was eluted twice with a 1:1 (v / v) mixture of ethyl acetate and ethanol, 4.5 mL each time, for 10 min each time. The resulting eluent was dried under vacuum at 40 °C to constant weight to obtain a concentrate of dissolved polar substances.

[0104] According to the three-stage enrichment method, the apparent single enrichment rate of dissolved polar substances in this application example is 80.5%, and the unit oil sample treatment time is 1.9 min / mL.

[0105] Application Example 6

[0106] This application example illustrates a method for enriching soluble organometallic complexes and sulfur-containing polar components.

[0107] Take 20 mL of oil sample from the faulty transformer and keep it at 40℃ for 15 min. Add 40 mL of petroleum ether to make the volume ratio of petroleum ether to oil sample 2:1. Add 400 mg of mercaptosilicone and 200 mg of pyridyl resin to the diluted oil sample, and shake and adsorb at 40℃ for 60 min at a shaking frequency of 200 rpm.

[0108] After adsorption, the adsorbent was collected by centrifugation at 6000 rpm for 10 min. It was pre-washed twice with petroleum ether, 6 mL each time. Subsequently, it was eluted twice with ethanol containing 0.5 vol.% ammonia, 3 mL each time, for 10 min each time. The eluent was dried under vacuum at 40 °C to constant weight to obtain a concentrate of dissolved polar substances.

[0109] According to the three-stage enrichment method, the apparent single enrichment rate of dissolved polar substances in this application example is 84.1%, and the unit oil sample treatment time is 2.2 min / mL.

[0110] Application Example 7

[0111] This application example illustrates the enrichment method using solid-phase extraction columns.

[0112] The composite functionalized solid-phase adsorbent was packed into a solid-phase extraction column at a loading amount of 300 mg. The composite functionalized solid-phase adsorbent was obtained by mixing aminated silica, styrene-divinylbenzene copolymer and mercaptosilicone in a mass ratio of 1:1:0.5.

[0113] Take 10 mL of transformer oil sample, dilute with 20 mL of isooctane, and pass it through a solid-phase extraction column at a flow rate of 1.0 mL / min. After the sample passes through, prewash the column with 3 mL of isooctane, then elute sequentially with 2 mL of methanol and 2 mL of ethanol. Collect the eluent and dry it under vacuum at 40 °C to constant weight to obtain a concentrate of dissolved polar substances.

[0114] According to the three-stage enrichment method, the apparent single enrichment rate of dissolved polar substances in this application example is 81.8%, and the unit oil sample treatment time is 2.4 min / mL.

[0115] Application Example 8

[0116] This application example illustrates a method for enriching magnetically functionalized adsorbents.

[0117] A magnetic silica adsorbent coated with polydopamine-polyethyleneimine was used as a functionalized solid-phase adsorbent. A 20 mL sample of operating transformer oil was diluted with 40 mL of n-heptane. 500 mg of the magnetic functionalized adsorbent was added, and the mixture was shaken at 40 °C for 30 min to adsorb.

[0118] The adsorbent was separated by an external magnetic field. The solution was pre-washed twice with 5 mL of n-heptane each time, followed by elution twice with 2.5 mL of methanol each time. The eluent was then vacuum-dried at 40 °C to constant weight to obtain a concentrate of dissolved polar substances.

[0119] According to the three-stage enrichment method, the apparent single enrichment rate of dissolved polar substances in this application example is 79.6%, and the unit oil sample treatment time is 1.6 min / mL.

[0120] Comparative Example 1

[0121] The difference between this comparative example and application example 1 is that no functionalized solid-phase adsorbent is added, and only the diluted oil sample is directly concentrated at low temperature. The volume of the remaining oil samples and the dilution conditions are the same as in application example 1.

[0122] Because transformer oil matrix contains a high content of non-polar components, direct concentration leads to simultaneous enrichment of the oil phase background. Calculated using a three-stage continuous enrichment method, the apparent primary enrichment rate of dissolved polar substances in this comparative example was 52.4%, with a unit oil sample treatment time of 1.5 min / mL. This result indicates that simple low-temperature concentration leads to simultaneous enrichment of the oil phase background, making it difficult to achieve selective enrichment of dissolved polar substances; using functionalized solid-phase adsorbents can reduce the oil phase background and improve the enrichment effect of the target components.

[0123] Comparative Example 2

[0124] The difference between this comparative example and Application Example 1 is that the composite functionalized solid-phase adsorbent is replaced with unmodified silica gel, while all other conditions are the same as in Application Example 1.

[0125] Unmodified silica gel primarily relies on surface hydroxyl groups for non-specific adsorption, exhibiting insufficient adsorption capacity for plasticizers, soluble metal complexes, and some sulfur-containing polar components. Calculated using a three-stage enrichment method, the apparent single-stage enrichment rate of dissolved polar substances in this comparative example was 61.8%, with a unit oil sample treatment time of 1.8 min / mL. These results indicate that unmodified silica gel has insufficient adsorption capacity for various types of dissolved polar substances; composite functionalized adsorbents, through the synergistic effect of multiple functional sites, can improve the enrichment efficiency of dissolved polar substances.

[0126] Comparative Example 3

[0127] The difference between this comparative example and Application Example 4 is that the polyethyleneimine modified silica gel is replaced with ordinary C18 bonded silica gel, while all other conditions are the same as in Application Example 4.

[0128] Ordinary C18 bonded silica gel has a weak effect on acidic oxidation products and small carboxylic acid molecules. Calculated using a three-stage enrichment method, the apparent single-stage enrichment rate of dissolved polar substances in this comparative example was 63.5%, with a unit oil sample treatment time of 2.0 min / mL. This result indicates that ordinary C18 bonded silica gel has a weak effect on acidic oxidation products and oxygen-containing polar molecules; adsorbents containing amino groups or weak anion exchange sites are more suitable for the enrichment of such substances.

[0129] Comparative Example 4

[0130] The difference between this comparative example and Application Example 5 is that the styrene-divinylbenzene porous polymer resin is replaced with aminated silica, while all other conditions are the same as in Application Example 5.

[0131] Aminated silica is effective against acidic substances, but its π-π interactions and hydrophobic-lipophilic balance are insufficient for plasticizers and aromatic polar components. Calculated using a three-stage enrichment method, the apparent single-stage enrichment rate of dissolved polar substances in this comparative example was 66.2%, with a unit oil sample treatment time of 1.9 min / mL. These results indicate that aminated silica has insufficient adsorption selectivity for plasticizers and aromatic polar components; aromatic porous polymer resins are more suitable for enriching these components through hydrophobic-lipophilic balance and π-π interactions.

[0132] Comparative Example 5

[0133] The difference between this comparative example and Application Example 6 is that the mercaptosilicone and pyridyl resin are replaced with ordinary alumina, while all other conditions are the same as in Application Example 6.

[0134] Ordinary alumina exhibits adsorption for some polar small molecules, but lacks specific coordination for soluble metal complexes and sulfur-containing polar components. Calculated using a three-stage enrichment method, the apparent single-stage enrichment rate of dissolved polar substances in this comparative example was 64.7%, with a unit oil sample treatment time of 2.2 min / mL. These results indicate that ordinary alumina lacks specificity against soluble metal complexes and sulfur-containing polar components; thiol and pyridyl functional sites are beneficial for improving the adsorption and enrichment of these components.

[0135] Comparative Example 6

[0136] The difference between this comparative example and application example 1 is that a low-polarity prewash was not performed, and after adsorption, a methanol-ethyl acetate mixed eluent was used directly for elution. All other conditions were the same as in application example 1.

[0137] Because of the significant amount of residual transformer oil on the adsorbent surface, direct elution would carry some non-polar oil phase components into the enrichment solution. Calculated using a three-stage enrichment method, the apparent primary enrichment rate of dissolved polar substances in this comparative example was 69.4%, with a unit oil sample processing time of 1.5 min / mL. This result indicates that the lack of low-polarity pre-washing leads to the entry of residual oil phase from the adsorbent surface into the eluent, increasing the background for subsequent detection; low-polarity pre-washing helps to increase the relative content of dissolved polar substances in the extract.

[0138] Comparative Example 7

[0139] The difference between this comparative example and application example 1 is that the oil sample was directly extracted with ethanol and no solid-phase adsorbent was used. The remaining oil sample volume and dilution conditions were the same as in application example 1.

[0140] In direct liquid-liquid extraction, the contact between ethanol and the oil phase is insufficient, and some oil phase components are easily entrained, resulting in poor enrichment selectivity. Calculated using a three-stage enrichment method, the apparent single-stage enrichment rate of dissolved polar substances in this comparative example was 58.6%, with a unit oil sample processing time of 2.1 min / mL. These results indicate that direct liquid-liquid extraction easily entrains oil phase components, leading to insufficient enrichment selectivity and repeatability; functionalized solid-phase adsorption is more suitable for enriching low-content dissolved polar substances in complex oil matrices.

[0141] Comparative Example 8

[0142] The difference between this comparative example and Application Example 7 is that the sample flow rate through the solid phase extraction column is increased to 5.0 mL / min, while all other conditions are the same as in Application Example 7.

[0143] When the flow rate is too high, the contact time between the oil sample and the adsorbent is insufficient, and some dissolved polar substances cannot be fully adsorbed. Calculated using the three-stage enrichment method, the apparent single-stage enrichment rate of dissolved polar substances in this comparative example was 60.9%, with a unit oil sample processing time of 1.2 min / mL. This result indicates that excessively high flow rates during solid-phase extraction column processing reduce the contact time between the oil sample and the adsorbent, leading to incomplete adsorption; controlling the sample flow rate is beneficial for improving the enrichment effect of dissolved polar substances.

[0144] The comparison of the experimental results of the above application examples and comparative examples shows that the method of enriching and extracting dissolved polar substances in transformer oil using the functionalized solid-phase adsorbent described in this invention has significant technical advantages in terms of enrichment selectivity, processing efficiency and scenario adaptability.

[0145] Functionalized solid-phase adsorbents are the core of achieving efficient and selective enrichment. Application Example 1 uses a composite functionalized adsorbent, achieving an apparent primary enrichment rate of 82.6%; Comparative Example 1, without adsorbent, showed no selective enrichment ability with only 52.4% when directly concentrated at low temperature; Comparative Example 2, using unmodified silica gel, achieved only 61.8% enrichment through non-specific adsorption, demonstrating a clear synergistic gain effect from the composite functional sites. For different types of polar components, Application Example 4 uses polyethyleneimine-modified silica gel for the directional enrichment of acidic oxidation products, achieving an enrichment rate of 83.4%; Comparative Example 3, using ordinary C18 bonded silica gel, achieved only 63.5%. Application Example 5 uses styrene-divinylbenzene resin for the enrichment of plasticizers and aromatic components, achieving an enrichment rate of 80.5%; Comparative Example 4, using aminated silica, achieved only 66.2%. Application Example 6 uses mercaptosilicone and pyridyl resin to enrich metal complexes and sulfur-containing components, with an enrichment rate of 84.1%; in Comparative Example 5, when ordinary alumina was used, the enrichment rate was only 64.7%. The matching between functional sites and target substances directly determines the enrichment effect.

[0146] Pre-washing with a low-polarity solvent is a necessary step to ensure the purity of the enriched product. In Application Example 1, the enrichment rate was 82.6% after pre-washing with n-heptane; in Comparative Example 6, pre-washing was omitted and elution was performed directly, resulting in an enrichment rate of 69.4%, and the residual oil phase on the adsorbent surface entered the eluent, which would increase the matrix background interference in subsequent detection.

[0147] Reasonable control of process parameters can balance enrichment effect and operational efficiency. Application Example 7, using solid-phase extraction column mode and a sample flow rate of 1.0 mL / min, achieved an enrichment rate of 81.8%. Comparative Example 8, by increasing the flow rate to 5.0 mL / min, resulted in insufficient contact between the oil sample and the adsorbent, reducing the enrichment rate to 60.9%. Furthermore, Application Example 2 treated a small 5 mL oil sample, achieving an enrichment rate of 76.4%; Application Example 3 treated a large 50 mL faulty oil sample, achieving an enrichment rate of 81.2%; and Application Example 8, using a magnetic adsorbent combined with magnetic separation, achieved an enrichment rate of 79.6% with a unit oil sample processing time as low as 1.6 min / mL, meeting performance requirements in various application scenarios.

[0148] Compared to traditional liquid-liquid extraction, this method has superior overall performance. In application example 1, the solid-phase adsorption enrichment rate was 82.6%; in comparative example 7, the direct liquid-liquid extraction with ethanol yielded only 58.6%, and it also suffered from difficulties in separating the two phases, easy entrainment of oil phase, and poor reproducibility.

[0149] In summary, the eight application examples covered different oil sample volumes, adsorbent types, composite ratios, and operating modes. The apparent primary enrichment rate of dissolved polar substances was no less than 76%, and the unit oil sample treatment time was no more than 2.8 min / mL. All indicators met expectations. The eight comparative examples verified the necessity and technical superiority of the proposed scheme from the dimensions of adsorbent materials, key processes, process parameters, and extraction methods. The method has a wide range of applications, is convenient to operate, and has stable and reliable performance.

Claims

1. A method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent, characterized in that, Includes the following steps: S1. Constant temperature homogenization treatment of oil sample: Take 5-100mL of operating transformer oil sample, place it in a container, and treat it at a constant temperature of 25-55℃ for 5-30min to make the oil sample homogenized. S2. Low polarity dilution: Add a low polarity diluent to the oil sample to obtain a diluted oil sample; the volume ratio of the low polarity diluent to the operating transformer oil sample is 1:1 to 3:

1. S3. Solid-phase adsorption: Add functionalized solid-phase adsorbent to the diluted oil sample, and control the adsorption temperature at 25-50℃ and the adsorption time at 10-90min; the mass-to-volume ratio of the functionalized solid-phase adsorbent to the operating transformer oil sample taken in step S1 is 5-50mg / mL. S4. Adsorbent separation: Through solid-liquid separation, the functionalized solid-phase adsorbent loaded with dissolved polar substances is separated from the diluted oil after adsorption to obtain the loaded adsorbent. S5. Degreasing and pre-washing: The loaded adsorbent is washed 1 to 2 times with a low polarity pre-washing agent, with each washing time being 10 to 20 minutes, to remove the transformer oil and non-polar components remaining on the surface of the adsorbent, and to obtain the pre-washed adsorbent. S6. Polar elution: The pre-washed adsorbent is eluted with an eluent to obtain a solution of dissolved polar substances. S7. Enrichment solution treatment: The enrichment solution is concentrated and brought to a constant volume to obtain a solution of dissolved polar substances for subsequent detection. The concentration temperature is 25-45℃.

2. The method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent according to claim 1, characterized in that, The low-polarity diluent is one or more of n-hexane, n-heptane, isooctane, petroleum ether, or cyclohexane.

3. The method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent according to claim 1, characterized in that, The functionalized solid-phase adsorbent is selected from one or more of amino-containing adsorbents, aromatic porous polymer adsorbents, and chelating adsorbents containing thiol or pyridyl groups.

4. The method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent according to claim 3, characterized in that, The amino-containing adsorbent is aminated silica or polyethyleneimine-modified silica gel. The aromatic porous polymer adsorbent is a styrene-divinylbenzene copolymer; The thiol- or pyridyl-containing chelating adsorbent is a thiol-based silica gel, a pyridyl resin, or a polydopamine-modified adsorbent.

5. The method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent according to claim 1, characterized in that, The functionalized solid-phase adsorbent is a composite functionalized solid-phase adsorbent, which is obtained by mixing aminated silica, styrene-divinylbenzene copolymer and mercaptosilicone in a mass ratio of 1:(0.5~2):(0.2~1).

6. The method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent according to claim 1, characterized in that, The low-polarity pre-washing agent is one or a mixture of n-hexane, n-heptane, isooctane or petroleum ether; the amount of low-polarity pre-washing agent used is 0.5 to 2.0 mL per 100 mg adsorbent.

7. The method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent according to claim 1, characterized in that, The eluent is one or more of the following: methanol, ethanol, isopropanol, ethyl acetate, ethanol-water mixture, methanol-water mixture, alcohol solution containing 0.1-1.0 vol.% formic acid, and alcohol solution containing 0.1-1.0 vol.% ammonia.

8. The method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent according to claim 7, characterized in that, The volume fraction of water in the ethanol-water mixture or methanol-water mixture is 5-30 vol.%; the amount of eluent used is 0.3-2.0 mL per 100 mg adsorbent, and elution is performed 1-2 times, with each elution time being 5-30 min.

9. The method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent according to claim 1, characterized in that, The concentration and volume fixation process is carried out by nitrogen purging or low-temperature rotary evaporation.

10. The method for extracting dissolved polar substances from transformer oil using a functionalized solid-phase adsorbent according to claim 1, characterized in that, The extract is used for the detection of polar contaminants, and the detection methods include Fourier transform infrared spectroscopy, gas chromatography-mass spectrometry, liquid chromatography, liquid chromatography-mass spectrometry, ultraviolet spectroscopy, and total acid value detection.